1984
DOI: 10.1113/jphysiol.1984.sp015099
|View full text |Cite
|
Sign up to set email alerts
|

In vivo development of cholinesterase at a neuromuscular junction in the absence of motor activity in Xenopus laevis.

Abstract: SUMMARY1. Embryos of Xenopus laevis were selected prior to the onset of innervation and were raised for 2 days in the anaesthetic tricaine methanesulphonate (200 ,ug/ml). The gross development of these tricaine-reared animals appeared normal despite the absence of spontaneous motor activity and the lack of motor responses to prodding with a pin. Motor activity quickly appeared when the anaesthetic was withdrawn.2. Intracellular recording from the myotomes of intact, tricaine-maintained animals failed to reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

1985
1985
1996
1996

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…The importance of muscle activity is indeed already well known for synaptic AChE accumulation in mammals and chicks L0mo & Slater, 1980;Rubin et al 1980) but an impulse-independent factor also appears to contribute significantly. This is indicated by the findings that: (1) nerve terminals clearly possess the ability to instruct the myofibre on where to accumulate the AChE (see in particular L0mo & Slater, 1980); (2) in some species such as Xenopus, apparently normal amounts of synaptic AChE can form in complete absence of evoked action potential activity (Cohen, Greschner & Tucci, 1984); and (3) even in mammals some AChE accumulation does occur during synaptogenesis under the major conduction block of the present experiments, even though muscle fibrillatory activity could also be playing a role. Partial denervation of blocked muscle Partial denervation of blocked muscle would alone be sufficient to account for an equal magnitude of the changes of TTX-blocked and denervated muscles, by boosting the extrajunctional changes in innervated ITX-blocked myofibres (see Introduction and Cangiano et al 1984).…”
Section: Discussionmentioning
confidence: 98%
“…The importance of muscle activity is indeed already well known for synaptic AChE accumulation in mammals and chicks L0mo & Slater, 1980;Rubin et al 1980) but an impulse-independent factor also appears to contribute significantly. This is indicated by the findings that: (1) nerve terminals clearly possess the ability to instruct the myofibre on where to accumulate the AChE (see in particular L0mo & Slater, 1980); (2) in some species such as Xenopus, apparently normal amounts of synaptic AChE can form in complete absence of evoked action potential activity (Cohen, Greschner & Tucci, 1984); and (3) even in mammals some AChE accumulation does occur during synaptogenesis under the major conduction block of the present experiments, even though muscle fibrillatory activity could also be playing a role. Partial denervation of blocked muscle Partial denervation of blocked muscle would alone be sufficient to account for an equal magnitude of the changes of TTX-blocked and denervated muscles, by boosting the extrajunctional changes in innervated ITX-blocked myofibres (see Introduction and Cangiano et al 1984).…”
Section: Discussionmentioning
confidence: 98%
“…Sohal & Wrenn (1984) also reports that the high molecular weight form of AChE developed in both paralysed and aneural extraocular muscle of duck embryos. In developing Xenopus muscle, Cohen et al (1984) demonstrated that AChE activity increased despite immobilization by tricaine, a local anaesthetic. However, m.e.p.c.…”
Section: Discussionmentioning
confidence: 99%
“…Correspondence should be addressed to Dr. D. F. Davey Rubin et al, 1980;Steinbach, 1974). This is also the case for the nerve-induced changes in ChE localization that occur in Xenopus myotomal muscle (Cohen et al, 1984;. By contrast, muscle impulse activity is important for the localization of ChE in rat (Cangiano et al, 1980;Lamo and Slater, 1980b;Weinberg and Hall, 1979) and avian muscles (Betz et al, 1980;Gordon et al, 1974;Rubin et al, 1980; but see Sohal and Wrenn, 1984).…”
mentioning
confidence: 99%